1971
DOI: 10.1042/bj1210321
|View full text |Cite
|
Sign up to set email alerts
|

The α-amylase of the beetle Callosobruchus chinensis properties

Abstract: C. chinensis larval amylase is activated by Ca(2+) and inhibited by Cl(-) and EDTA (K(i) 6.7x10(-3)m). GSH and 2-mercaptoethanol activate, presumably at different sites, as 2-mercaptoethanol interferes with Ca(2+) activation, whereas GSH enhances it. The inhibition by iodoacetic acid and N-ethylmaleimide (K(i) 1.55x10(-2)m) suggest that free thiol groups are essential for activity. The pH optimum of 5.2-5.4 is moved to 5.6-5.8 by Ca(2+) and 2-mercaptoethanol. The activation energy is 7270 cal/mol, and is not a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
18
1

Year Published

1986
1986
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(23 citation statements)
references
References 10 publications
4
18
1
Order By: Relevance
“…The optimum pH of 6.8 of haemolymph amylase observed in the present study is in contrast to slightly acidic range reported in a variety of insect species (Baker, 1987;Podoler and Applebaum, 1971;Buonocore et aL, 1976). The sharp ascending and descending nature of the amylase activity indicate that the haemolymph amylase isozymes have similar pH optima.…”
Section: Discussioncontrasting
confidence: 54%
“…The optimum pH of 6.8 of haemolymph amylase observed in the present study is in contrast to slightly acidic range reported in a variety of insect species (Baker, 1987;Podoler and Applebaum, 1971;Buonocore et aL, 1976). The sharp ascending and descending nature of the amylase activity indicate that the haemolymph amylase isozymes have similar pH optima.…”
Section: Discussioncontrasting
confidence: 54%
“…A similar behavior was described in the carboxylesterase Est 30 from Geobacillus stearothermophilus, which in spite of being a dimer, was not affected neither for 2-mercaptoetanol nor DTT (Ewis et al, 2004). Furthermore, this reducing reagent is regarded as acting by protecting essential thiol groups in their reduced state (Podoler & Applebaum, 1971). Thus 2-mercaptoethanol seems to increase type II esterase activity by protecting the thiol groups that could be involved in the enzyme activity.…”
Section: Effect Of Metal Ions and Inhibitors On Esterase Activitymentioning
confidence: 51%
“…They are widely used in the food and textile industries . The first insect α‐amylase studied in some detail was reported from the pulse beetle, Callosobruchus chinensis , in which the enzyme was purified and its properties were reported . Insect α‐amylases digest polysaccharides.…”
Section: Introductionmentioning
confidence: 99%